Why low-intensity endurance training for athletes? - Matomäki, Pekka (Springer Science and Business Media LLC, 2025)
Endurance athletes prioritize most of their training in low-intensity zone. This forms a paradox, as immediate logic would argue against it: Acutely low-intensity exercise does not challenge the homeostasis or cardiopulmonary system of high-level athletes sufficiently to produce performance gains comparable to those from moderate- or high-intensity exercise. In this perspective study, seven possible explanations for the purpose of excessive-volume low-intensity training in endurance athletes are proposed. The hypotheses are not all mutually exclusive. They range from a psychological need for easy days and the incremental benefits of low-intensity training without accumulating stress, to the possibility that such training may ultimately be replaceable.